Integrated GIS and remote sensing analysis for landfill sitting in Western Crete, Greece - Alexakis, Dimitrios; Sarris, Apostolos (My University, 2014)
The assessment of the optimum landfill sitting requires multiple environmental data organized in a proper and efficient way to be effectively processed. Geographical information systems define an ideal tool for handling vast amounts of such kind of information combining multiple heterogeneous spatiotemporal data. Additionally, archive satellite remote sensing images set an ancillary approach to effective environmental monitoring of land surface within the areas of already established landfills and their surroundings (e.g. for calculation of crucial parameters such as vegetation indices). In this study, 17 environmental and anthropogenic factors were used to identify the most suitable sites for optimum landfill sitting in the western part of the island of Crete-Greece. The method used for the evaluation of all different factors is the analytical hierarchy process enhanced with fuzzy logic techniques. The results were compared with the already established landfills (legal/controlled and illegal/non-controlled) in the area of Chania prefecture and the results demonstrated that 75 % of the already (legal or illegal) established landfills of the prefecture are situated in extremely inappropriate areas from environmental point of view.
Keywords: AHP; Crete; GIS; Landfills; Remote sensing